2007
DOI: 10.1897/06-430r.1
|View full text |Cite
|
Sign up to set email alerts
|

Biokinetics and tolerance development of toxic metals in Daphnia magna

Abstract: Abstract-Daphnia magna is widespread in many freshwater systems of temperate regions and frequently is used to test metal toxicity. Recently, studies have been performed to determine metal biokinetics and development of tolerance in this important zooplankton species. In the present paper, we review the recent progress in these areas and suggest possible directions for future studies. Substantial differences exist in aqueous uptake, dietary assimilation, and elimination of several metals (Cd, Se, Zn, Ag, Hg, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 93 publications
(228 reference statements)
3
64
2
2
Order By: Relevance
“…However, organic matter, derived from the diet, may not have an important role as a chelator, considering the organisms of these tests, which are filter feeders. Furthermore, filtration activity can be changed in the presence of food, reducing passage times of both food and ametal, reducing their absorption by this test organism (Tsui and Wang 2007), the hypothesis more plausible for the present study.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…However, organic matter, derived from the diet, may not have an important role as a chelator, considering the organisms of these tests, which are filter feeders. Furthermore, filtration activity can be changed in the presence of food, reducing passage times of both food and ametal, reducing their absorption by this test organism (Tsui and Wang 2007), the hypothesis more plausible for the present study.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore considering the chitin constitution of cladocerans carapace, the toxicity of arsenic may be enhanced by adsorption of this ametal to exoskeleton of test organisms, and iron could increase this adsorption, although some authors associate the metal adsorption to limestone from carapace (Tsui and Wang 2007). Carney et al (1986) assessed cadmium uptake in Daphnia magna and found that most of this metal was adsorbed to the shell bodies, and tolerance was related to molting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations